Reoxidation of steel by adding an overcritical concentration of deoxidizer - Grozdanić, Vladimir (Materiali in tehnologije, 2001)
At deoxidation of molten steel using silicon or aluminium appears an paradox. Namely, increasing concentration of deoxidizer in the melt over some ciritical value results in increase of dissolved oxigen. Thermodynamical conditions for appearance of this phenomenon has been discussed in detail.
Keywords: dezoksidacija; jeklo